Utilising a livestock model for wildlife health planning - Patterson, Stuart (Frontiers in Veterinary Science, 2024)
Health planning provides a structure for the application of epidemiological data to managed populations with the intention of maximising health and identifying targets for intervention. Whilst this is established practice in livestock health, such schemes are rarely applied to free-living wild animal populations. The health of wildlife is important for a variety of reasons including conservation, human health, and ecosystem health, and so it is recommended that a formalised health planning approach be adopted for wildlife, based upon advantages of livestock health schemes identified here. Six key strengths of livestock herd health plans are identified in that these plans are: (1) Outcome driven, (2) Structured and repeatable, (3) They can incorporate both health and welfare considerations and in doing so, establish multidisciplinary management teams, (4) Evidence-based allowing for the prioritisation of key risk factors, (5) Encompassing of both population and individual metrics, and (6) Offer the opportunity for accreditation schemes. The benefits highlighted have implications for both wildlife management and research agendas where the structured format of the health plans will highlight knowledge gaps. Challenges are acknowledged, and it is recognised that livestock health planning cannot simply be copied across to a wildlife context. However, the strengths identified are great enough that it is recommended that wildlife population health planning is developed for active management of individual populations, learning lessons from existing plans.